Electrothermal Silver Nanowire Thin Films for In-Situ Observation of Thermally-Driven Chemical Processes - Martínez, E.D.; García Flores, A.F.; Pastoriza, H.; Urbano, R.R.; Rettori, C. (Elsevier, 2018)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina